MANAJEMEN SEBAGAI PENDEKATAN DALAM MEWUJUDKAN MUTU PENGELOLAAN KESISWAAN DAN SDM DI LEMBAGA PENDIDIKAN - Dzikrul Khakim; Muhammad Yasin; Cindy Erlinda Mayangsari (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Student management and human resources are an important part of building and developing the quality of Islamic education. In essence, student management and human resources are still considered not optimal, especially for Islamic educational institutions. The purpose of this research is to help educational institutions achieve their goals and vision optimally. The method that researchers use is library research in the form of references from various sources of library data that are ready to use so that they can be used immediately and are not limited by space and time. The stages in management, namely planning, organizing, controlling, and directing, must be carried out properly so that the implemented programs can be successful. In the planning stage, educational institutions must make clear and measurable plans based on student needs and existing HR policies. Furthermore, the organizing stage must determine an effective organizational structure to achieve its goals and vision. The control stage is an important stage because educational institutions must regularly monitor and evaluate the performance of students and human resources. Finally, in the briefing stage, educational institutions must provide clear and directed directions to students and human resources so that they can achieve the goals that have been set. Therefore, management is very important in realizing the quality of student and human resource management in educational institutions.